2000
DOI: 10.1300/j008v16n01_08
|View full text |Cite
|
Sign up to set email alerts
|

Responses of School Psychologists and Special Education Teachers to Administrative Pressures to Practice Unethically

Abstract: Responses of school psychologists (N = 141) and special educators (N = 130) to ethical dilemmas involving conflicts between administrative directives and ethical obligations were examined. Respondents completed a survey asking them to predict their own and others' responses to four ethical dilemmas. The majority of respondents predicted that they, immediate colleagues, and professional peers would make the choices judged as ethical in all situations. Predictions of ethical response were highest for self predic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
14
0

Year Published

2004
2004
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(14 citation statements)
references
References 15 publications
0
14
0
Order By: Relevance
“…For the quantitative study reported in Helton et al (2000), participants predicted their own and others' responses to each dilemma by choosing one of two possible options. For each dilemma, one option provided by the authors represented an ethical response while the other option provided represented an unethical response.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…For the quantitative study reported in Helton et al (2000), participants predicted their own and others' responses to each dilemma by choosing one of two possible options. For each dilemma, one option provided by the authors represented an ethical response while the other option provided represented an unethical response.…”
Section: Discussionmentioning
confidence: 99%
“…Previous research (e.g., Helton et al, 2000;Kelman & Hamilton, 1989) suggests that several factors must be in place before practitioners can cope appropriately with administrative pressures to practice unethically. These factors include the ability to recognize situations posing ethical dilemmas, the motivation to honor ethical obligations, and the skills to do so.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Our own research on the topic of administrative pressures to practice unethically is described in two articles (Helton & Ray, 2005b;Helton, Ray, & Biderman, 2000) and two conference papers (Helton & Ray, 2005a;Helton & Ray, 2007). The remainder of this article summarizes this research and makes some suggestions for practice.…”
mentioning
confidence: 99%